Neonatal Morbidity Associated With Vaginal Delivery of Noncephalic Second Twins. Issue 1 (March 2019) - Schmitz, T.; Korb, D.; Battie, C.; Cordier, A.G.; de Carne Carnavalet, C.; Chauleur, C.; Equy, V.; Haddad, B.; Lemercier, D.; Poncelet, C.; Rigonnot, L.; Goffinet, F.
Abstract : ( Am J Obstet Gynecol . 2018;218:449.e1–e13) The American College of Obstetricians and Gynecologists and the Society for Maternal-Fetal Medicine have recommended vaginal deliveries be attempted in women with cephalic/cephalic and cephalic/noncephalic presenting twins. However, survey data revealed >40% of US practitioners are reluctant to perform breech extractions in noncephalic second twins and prefer to perform cesarean deliveries. A national prospective Jumeaux Mode d'Accouchement (JUMODA) study was conducted to evaluate the management of twin deliveries and assess neonatal mortality and morbidity according to second twin presentation after vaginal birth of the first twin at ≥32 weeks of gestation. This was a planned secondary analysis of the JUMODA cohort.